Growth and Yield Performance of Pleurotus ostreatus Cultivated on Agricultural Residues - Hailu Gebru; Tolosa Belete; Gezahegn Faye (Mycobiology)
Food insecurity and malnutrition are among the major problems in most developing nations recently. Mushroom cultivation is one of the promising strategies to overcome these challenges. The growth and productivity of mushrooms differ because of their wide range of cultivation substrates. Cultivating Pleurotus ostreatus on suitable substrates is one of the key factors affecting its growth and productivity. This study was, therefore, conducted to investigate the effect of cultivation substrates, namely straws of tef (Trt1), barley (Trt2), and wheat (Trt3), husks of faba bean (Trt4) and field pea (Trt5), and sawdust (Trt6) alone, and their mixture (1:1, w/w) (Trt7) on the growth and yield of P. ostreatus. Mycelial colonization, primordial formation, and days to first harvest were faster (13.00, 19.67, and 22.67 days) for the P. ostreatus cultivated on Trt7 whereas those grown on Trt6 were delayed (18.00, 27.00, and 29.67 days), respectively. Trt7 gave a higher (67.33) fruiting body/bunch and total yield (2001.70 g/bag). Biological efficiency was also significantly (p < 0.05) higher for Trt7 (238.64%). Strong relationships between cap diameter and mushroom yield (r = 0.84***), number of bunches (r = 0.76***), number of fruiting bodies (r = 0.80***), stipe length (r = 0.83***), and total yield (r = 0.84***) were among significant positive correlations observed. In conclusion, cultivating P. ostreatus on the Trt7 (mixed substrate) is recommended rather than using either of the residues alone.